Gigahertz and terahertz technologies for broadband communications - Edwards, T. C. (Terence Charles) (Artech House space technology and applications library., 2000)
"Gigahertz and Terahertz Technologies for Broadband Communications explores and demystifies the radio and light frequency technologies necessary to satisfy the ever-increasing demand for faster, higher capacity broadband communications today and into the 21st century." "This highly understandable book delivers a concise, critical appraisal of current and developing broadband systems, including terrestrial, satellite, and subspace systems. It examines competing technologies and how they interact, probes critical topics such as digital signaling, and takes a close look at the key players vying to provide high-speed internet access, digital TV, and other new telecommunications services in the coming years."--Jacket